Political economy, poverty, and polycentrism in the global environment facility’s Least Developed Countries Fund (LDCF) for climate change adaptation - Sovacool, Benjamin K.; Tan-Mullins, May; Ockwell, David; Newell, Peter (Taylor & Francis, 2017)
Climate change adaptation refers to altering infrastructure, institutions or ecosystems to respond to the impacts of climate change. Least developed countries often lack the requisite capacity to implement adaptation projects. The Global Environment Facility’s Least Developed Countries Fund (LDCF) is a scheme where industrialised countries have disbursed $934.5 million in voluntary contributions to support 213 adaptation projects across 51 least developed countries. But how effective are its efforts—and what sort of challenges have arisen as it implements projects? To provide some answers, this article documents the presence of four “political economy” attributes of adaptation projects—processes we have termed enclosure, exclusion, encroachment and entrenchment—cutting across economic, political, ecological and social dimensions. Based on extensive field research, we find the four processes at work simultaneously in our case studies of five LDCF projects being implemented in Bangladesh, Bhutan, Cambodia, the Maldives and Vanuatu. The article concludes with a discussion of the broader implications of the political economy of adaptation for analysts, program managers and climate researchers at large. In sum, the politics of adaptation must be taken into account so that projects can maximise their efficacy and avoid marginalising those most vulnerable to the impacts of climate change.